The Critical Path Method In Management Information System of Contractor Service Company Using Incremnetal Model - Hamim Tohari; Ahmad Kudhori; Hedi Pandowo (Information System; Universitas Buana Perjuangan Karawang, 2023)
Good control is needed in managing a project, starting from controlling the human resources to systematic scheduling. CV. XYZ Surabaya is a contractor service company, that does not yet have an information system that can be used as a control tool in project management. Critical Path Method (CPM) is one method that can be used to schedule projects. This study aims to design a project management information system by implementing CPM. The system design is done using the Incremental Model. The results of this study are in the form of a prototype system that fits the needs of CV. XYZ Surabaya, includes system flow, Contextual Data Model (CDM), and User Interface (UI).